AN INVESTIGATION OF SURFACE ROUGHNESS ON AISI 1045 STEEL USING DEFORM 3-D AND ITS COMPARISION WITH THE EXPERIMENT. Issue 1 (1st February 2022) - Vishwakarma, Premnarayan; Sharma, Ajay; Kannojiya, Ravindra; Ratna, Sanatan; Udaiyakumar, K.C.
Abstract: Conventional processes such as turning, and milling are often accompanied by defects such as tool marks and scratches on the final machined surface. This leads to tool wear and loss of energy which is quite undesired. This leads to poor product quality and a lowered tool life. Further, processes like honing and lapping can be used to improve the surface finish but the major drawback is the dependence on the skill of the workers involved. To overcome these issues, the burnishing operation is used for an adequate surface finish on the machined surface. The process is not only simple in operation but also chip less. In the current research work, turning operation is carried out on the ferrous material using an insert tipped tool in a CNC lathe machine. The operations are carried out at different machining parameters like speed, feed and depth of cut etc. Roughness patterns at various machining conditions are obtained and analysis was done to get the adequate machining parameters. The metal cutting process is analyzed with the FEM model for 3D simulation of the operation undertaken with a solid SPCT (single point cutting tool). This tool is modelled with CATIAV5, and exported STL files and imported in DEFORM 3D.